Scalar field perturbations in asymptotically Lifshitz black holes - Giacomini, Alex (2012)
We consider scalar field perturbations about asymptotically Lifshitz black holes with dynamical exponent z in D dimensions. We show that, for suitable boundary conditions, these Lifshitz black holes are stable under scalar field perturbations. For z=2, we explicitly compute the quasinormal mode frequencies, which result to be purely imaginary, and then obtain the damping-off of the scalar field perturbation in these backgrounds. The general analysis includes, in particular, the z=3 black hole solution of three-dimensional massive gravity.